Update on Homeopathic Treatments for Migraines (International Journal of Life Sciences Biotechnology and Pharma Sciences, 2022)
In addition to being the most common neurological ailment in adults, migraines affect a disproportionately largenumber of women from the time they reach menarche until they reach menopause. The debilitating effects ofchronic migraine, which must be experienced at least fifteen days a month, are well-documented. At least tendays a month, many people with chronic migraine take a compound analgesic, opioid, triptan, or ergot derivative,indicating that they are likely to abuse medicine. There is still a need for migraine therapy, despite the fastprogress in path physiology that has led to new options. The use of homeopathy to treat migraines is discussed inthis article.